Improving Teacher Performance By Implementing Reward and Punishment Effective and Measurable Program - M. Yusuf Alfian Rendra Anggoro KR; Hartanto Hartanto; M. Anton Fatoni; Hermiyetti Hermiyetti; Rosalina Anindia Sari Kartika (Journal on Education, 2023)
The objective of this investigation is to comprehend how implementing incentives and penalties enhances the efficiency of educators. The analysis conducted is qualitative and descriptive. The approaches employed to collect data are observation, interviews, and documentation. The analysis of the information was executed by employing techniques such as data reduction, data demonstration, and deduction of conclusions. To ensure the accuracy of the data, data triangulation was implemented. The findings of the research exhibit that rewards come in the form of financial incentives, such as wages, salaries, teacher stipends, and bonuses. Non-financial awards such as promotion, training to improve skills, holidays, cooperative colleagues and superiors, and a good work environment. As for the application of punishment or punishment in the form of intellectual punishment, getting a reprimand, postponement of promotions, or periodically. According to the aforementioned research findings, using rewards and penalties can improve teacher effectiveness. Researchers are aware of how crucial the use of rewards and penalties is to raising teacher performance. The use of rewards and sanctions can help improve teacher effectiveness.